Analysis of the Availability of the Majority Quorum System Resulting from Cross Union Operations - Setia Ningsih; Arsal, Armayani (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2024)
Cross union operation is an operasi to arrange a new majority coterie which we combine each quorum of another two different majority coterie. The purpose of this research is to analyse the availability comparison of quorum system between majority coterie and join majority coterie by cross union operation. By the analyse result, we know that majority coterie, which even universe set (number of element is even), has the same availability as join majority coterie which arranged by odd universe set (number of element is odd). While join majority coterie which arranged by even universe set, has relatively the same availability as majority coterie which even universe set. Finally, we conclude that the availability of majority coterie is relatively the same as join majority coterie by cross union.